The elders handbook a practical guide for church leaders - Berghoef, Gerard; De Koster, Lester (Grand Rapids, MI Christian Library Press, 1979)
Includes bibliographical references and index.
Keywords: Eldership -- handbooks; Christian Reformed Church -- government -- United States